INVESTIGATION OF MICROSTRUCTURE PROPERTIES OF NbC-B COATED HARDOX 400 STEEL BY TRD METHOD AND EVALUATION OF WEAR BEHAVIOR BY TAGUCHI METHOD - Celik, Yahya Hisman; Ertem, Mehmet; Gur, Ali Kaya; Kurt, Bulent; Caligulu, Ugur; Ozay, Cetin; Yildiz, Tulay (World Scientific Publ Co Pte Ltd, 2021)
In this study, Hardox 400 steel used as substrate material was coated through solid media Thermoreactive Diffusion (TRD) method using Ferro Niobium and Ferro Boron powders from carbide forming element powders. Coating was carried out in three different temperatures (950 degrees C, 1000 degrees C and 1050 degrees C) and three different time intervals (1, 2 and 3h). Microstructures of the coated specimens were examined by optical microscope, Scanning Electron Microscope (SEM), Energy Dispersive X-Ray Spectroscopy (EDX) and X-ray Diffraction (XRD); and hardness values were measured. The effects of coating parameters on coating thickness and hardness were analyzed by ANOVA. In addition, specimens were subjected to wear tests to determine the effect of hardness and coating parameters on wear. In the wear tests, Taguchi test design setup was used. The obtained results were compared with the Hardox 400 steel used under current conditions. It was seen from optical microscope and SEM images that Hardox 400 steel surface could be coated with TRD method depending on coating parameters. The average thickness of NbC-B coating ranged from 1.797 mu m to 5.596 mu m under different process temperature and time. Rising the coating time and temperature increased the coating thickness by 311.40%. EDX analysis showed that the coating layer was composed of B, C, Fe and Nb elements, and XRD analysis also showed that the phase in the coating layer is NbC-B. The NbC-B phase was determined to be an important factor in increasing the hardness. The coating hardness is enhanced by 320.80% depending on the coating parameters. Optimum coating thickness, hardness and wear results were obtained from high coating temperature and time. Uncoated Hardox 400 steels were worn out more compared to the coated Hardox 400 steels. The contribution of coating temperature and time to wear resistance was 1.46% and 8.02%, respectively. It was observed that the important parameter for wear volume was the applied load.
Keywords: Hardness; Hardox 400 steel; NbC-B coating; microstructure; TRD; wear